Successful treatment of diffuse alveolar hemorrhage secondary to Mycoplasma pneumoniae complicated with hemophagocytic lymphohistiocytosis in children: a case report and non-systematic literature review - Yang, Min; Liu, Zhong-Qiang; Wang, Yang; Luo, Li-Li; Qiao, Li-Na (Frontiers in Pediatrics, 2024)
Background After quarantine related measures were was completely lifted in China, the respiratory infection rate of children caused by Mycoplasma pneumoniae (MP) increased significantly, and MP infection may lead to rare severe intra and extrapulmonary manifestation. Hemophagocytic lymphohistiocytosis (HLH) and diffuse alveolar hemorrhage (DAH) are life-threatening clinical syndromes, timely recognition may contribute to timely treatment and improve prognosis. Currently there are no reports of Children with DAH secondary to MP infection complicated with HLH.We successfully treated a previously healthy school-age child who was admitted to the pediatric intensive care unit (PICU) with fever, cough, drowsiness and progressive dyspnea.HLH was confirmed by clinical ad testing criteria, DAH was indicated by computed tomography (CT)